The Influence of Budget Participation and Budgeting Procedural Justice on Kendari City Government Management Performance with Job-Relevant Information as an Intervening Variable - Ilmi, Azzahra Nikmtaul; Utami, Wiwik (Journal of Social Research, 2023)
This study aims to examine the effect of budgetary participation and procedural fairness of budgeting on the performance of Kendari city government management with job-relevant information as a mediating variable. the object of this study is the work unit of the Kendari City regional apparatus. The population in this study was Kendari City Government Agencies, totaling 31 SKPD. The sampling technique was using Purposive Sampling, thus obtaining a sample of 124 respondents. The data analysis technique in this study is Inferential Statistics using the Partial Least Square approach. The results of this study indicate that Budget participation has a positive and significant effect on job-relevant information. Budgetary participation has a positive and significant effect on managerial performance. budgeting procedural justice has a positive and significant effect on managerial performance. budgeting procedural justice has a positive and significant effect on job-relevant information. Job-relevant information has a positive and significant effect on managerial performance. job-relevant information can mediate the influence of influential budgetary participation on managerial performance. job-relevant information can mediate the effect of budgeting procedural justice on managerial performance l. The contribution of this research is to make a scientific contribution to regional financial accounting so that by knowing the importance of managerial performance, local governments can provide maximum service to the community which of course has an impact on increasing people's welfare.